Weevils to clear Africa's waterways - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Clogged up water-ways in West Africa are gradually being cleared by weevils brought in from South America. Water hyacinth (Eichornia crassipes) and water lettuce (Pistia stratiotes), which have been gradually colonizing rivers, canals and dams for...